Educational psychologists' involvement in critical incidents: self-efficacy and influencing factors. Issue 4 (2nd October 2021) - Bennett, Joanne; Edwards, Hannah; Finnegan, Charlotte; Jones, Rebecca; Carpenter, Caroline; Sargeant, Cora
ABSTRACT: Supporting school communities following a critical incident (CI) is a stressful, yet established, part of an educational psychologist's (EP's) role. The authors aim to explore whether emotional intelligence (EI), the number of CIs worked, and coping strategies predict EPs' CI self-efficacy, and to gather EPs' views on CI training. Ninety-five EPs working for UK local authorities completed an online survey that measured their self-efficacy towards CIs, their EI, and coping strategies. Information about how CIs are allocated, supervision, training received, and suggestions for future training were obtained. EI, approach coping strategies, and avoidant coping strategies were all predictors of CI self-efficacy. Results showed that 76.5% of EPs considered they needed more CI training and expressed they would benefit from knowledge- and experiential-based training. Implications are discussed, using a training framework informed by sources of self-efficacy, emphasising the need to be consciously aware of the EI and coping strategies that EPs already possess.